Retrospective analysis of early neurodevelopmental outcomes after esophageal atresia repair at a single institution: short-gap vs. long-gap defect - Lowdermilk, Mary Madelyn; Evanovich, Devon Michael; Wang, Jue Teresa; Pier, Danielle Bennett; Sadhwani, Anjali; Zendejas, Benjamin; Bajic, Dusica (Frontiers in Pediatrics, 2025)
BackgroundWith increased survival of infants born with esophageal atresia (EA), there is a knowledge gap regarding neurodevelopmental outcomes. We aimed to quantify the frequency of (1) documented developmental delay, and (2) implementation of early intervention services in the first and the second year of life following repair of short- and long-gap EA.MethodWe retrospectively analyzed term-born (n = 44) and premature infants (n = 26) following EA repair at a single institution (2009–2020). Infants with anomalies associated with known neurological disorders were excluded. Clinical data was obtained from the electronic medical record, and presented as means and percentages. Developmental delay included clinically documented motor, speech/language, and cognitive delays that were stratified according to a surgical group: short- and long-gap EA.ResultsNearly half of short-gap (24/54; 44%) and most of long-gap EA patients (12/16; 75%) had documented developmental delay in the first year of life that persisted into the second year of life [52% [28/54] short-gap; 69% [11/16] long-gap EA]. Developmental delay was noted irrespective of gestational age at birth, co-existing cardiac anomalies, or presence of cranial/brain findings on imaging. By age 2, 70% (38/54) of short-gap and 69% (11/16) of long-gap EA patients had received early intervention.InterpretationInfants born with EA are at high-risk for developmental delay. Early neurodevelopmental assessments and intervention is recommended for EA patients.